Analysis of Land Cover Change: Case Study in Concession Area of PT. GRUTI Unit Tele I North Sumatra - Siti Latifah; Zulkarnain Batubara; Anita Zaitunah; Seca Gandaseca (Talenta Publisher, 2026)
Changes in cover are the result of human activities and natural phenomena. Land cover in an area always changes over time. This study aims to identify and analyze the condition of land cover in 2013 and 2023 in the concession area of ​​PT. GRUTI Unit Tele I obtained through guided classification using ArcGIS 10.4 software and Microsoft Excel. The results of the study showed that throughout 2013-2023 in Unit Tele I there was a change in the area of ​​forest from 14,468.85 ha to 14,138.91 ha. In non-forest areas, there is an increase in area from 443.43 ha to 874.98 ha, and open areas have decreased from 410.22 ha to 402.21 ha. Changes in land cover are dominated by land occupation by the community due to a lack of supervision from concession managers and the absence of production activities in the area.